Performance evaluation of HVDC system with ESCR variation - Devarapalli R.; Pandey R.K. (My University, 2025)
This paper presents a study of HVDC system with variation in effective short circuit ratio (ESCR). The sample system considered is CIGRE benchmark model in PSCAD/ EMDC environment. An analysis has been presented for various ESCR values which show the sensitivity of converter control under low ESCR conditions. The investigations reveal improper converter operations, in case AC system strength is not maintained adequately. This may be used as guidelines for upcoming HVDC link in varying AC system strength conditions. © 2012 IEEE.